Assess the practice of breast feeding techniques among mothers undergone caesarean section in a selected hospitals at Puducherry - B, Meenatchi; Bala Dash, Manju (International Journal of Nursing Research, 2023)
Introduction: Breastfeeding is a unique experience, which should be valued and supported by both maternity and neonatal caregivers. It is nature’s most precious gift to the newborn. Mother’s milk, beyond doubt, is unparalleled in nutritional value and is the best start to life. Breastfeeding is an unequaled way of providing ideal food for the healthy growth and development of infants. Objective: To assess the knowledge of the practice of breastfeeding techniques. Methods: The study was conducted on 30caesarean section mothers admitted in selected hospitals at Puducherry. The study design was descriptive, purposive sampling technique was used. The instrument used for data collection was a standardized latch scale. Women practice of breastfeeding was assessed personally with the help of latch scale regarding their knowledge on breastfeeding practices. Results: Majority of 66.6% mothers having good knowledge, 13.3% having an average knowledge and 20% of mothers having poor knowledge on breastfeeding practice. Conclusions: It is desirable breastfeeding practice after the first week of the postpartum period to women who deliver via cesarean sections